Biochars as Potential Adsorbers of CH4, CO2 and H2S - Sethupathi, Sumathi; Ming, Zhang; Rajapaksha, Anushka Upamali; Sang, Ryong Lee; Mohamad Nor, Norhusna; Mohamed, Abdul Rahman; Al-Wabel, Mohammad; Sang, Soo Lee; Yong, Sik Ok (MDPI, 2017)
Methane gas, as one of the major biogases, is a potential source of renewable energy for power production. Biochar can be readily used to purify biogas contaminants such as H2S and CO2. This study assessed the adsorption of CH4, H2S, and CO2 onto four different types of biochars. The adsorption dynamics of biochars were investigated in a fixed-bed column, by determining the breakthrough curves and adsorption capacities of biochars. The physicochemical properties of biochars were considered to justify the adsorption performance. The results showed that CH4 was not adsorbed well by the subjected biochars whereas CO2 and H2S were successfully captured. The H2S and CO2 breakthrough capacity were related to both the surface adsorption and chemical reaction. The adsorption capacity was in the following order: perilla > soybean stover > Korean oak > Japanese oak biochars. The simultaneous adsorption also leads to a competition of sorption sites. Biochars are a promising material for the biogas purification industry.